Survival and Risk Factors Among Dialytic Acute Kidney Injury Patients After Cardiovascular Surgery - Silva,Andrea B. V. (2018)
Abstract Objective: Acute kidney injury (AKI) is a frequent postoperative complication after cardiovascular surgery. It has been described as a predictor of decreased survival rates, but how dialysis decreases survival when initiated on the postoperative period has yet to be determined. To analyze the survival of patients who presented postoperative AKI requiring dialysis up to 30 days after cardiovascular surgery and its risk factors is the aim of this study. Methods: Of the 5,189 cardiovascular surgeries performed in a 4-year period, 157 patients developed AKI requiring dialysis in the postoperative period. The Kaplan-Meier survival curve and log-rank test were used in the statistical analysis to compare the curves of categorical variables. P-value< 0.05 was considered significant. Results: Patient average survival was 546 days and mortality was 70.7%. The need for dialysis on the postoperative period decreased late survival. Risk factors for decreased survival included age (P<0.001) and postoperative complications (P<0.0003). Conclusion: The average survival was approximately one year among dialytic patients. Age and postoperative complications were risk factors that determined decreased survival.